Áudio, imersão e presença em jogos digitais - Rodrigues, Felipe Antunes de Oliveira (2018)
This dissertation has the objective of analyzing the experience of immersive audio in digital games, as perceived by the player as a listener and agent in the soundscape of virtual reality. The first chapter seeks to briefly examine and define the concepts of immersion and presence, in order to allow a deeper study of immersive audio to be possible. It also presents considerations about the coupling devices through which immersion in digital games is possible, in particular headphones, so common in the gamer routine. The second chapter is dedicated to the analysis of sound elements found in the virtual reality of digital games through the crossing of concepts and theories by authors such as Schafer, Meneguette, Huiberts, Droumeva among others. By doing so it seeks a comprehensive understanding of what can typically be heard in this medium in order to stimulate the immersive experience. The chapter also deals with problems and solutions that might interfere in the immersion in positive or negative ways, in order to clarify the relevance of the minutiae with respect to immersive audio. The third chapter approaches the subject from another angle, seeking an understanding of how the immersive experience of audio em digital games presents itself to the player. Next, analysis of of the game can hear the soundscape in the game are made. At the end of the chapter the concepts are reviewed, aiming to presenting an understanding of how the player is given the immersive experience of audio in digital games. The fourth and last chapter consists of a case study, in order to demonstrate, in a practical way, the immersive experience of audio studied so far